RANCANG BANGUN PERANGKAT MONITORING BESARAN LISTRIK PADA PANEL HUBUNG BAGI BERBASIS AUGMENTED OPERATOR ADVISOR - Hamdani; Nirwan A Noor, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
An electrical power operator/technician must possess sufficient skills and knowledge when measuring directly on the device in the panel. There are risks that can lead to workplace accidents. Considering the potential risks, there is a need for technology where operators do not have to manually open panels. Instead, they can use devices that allow technicians to access the required data virtually and in real-time. Therefore, this research aims to create a prototype utilizing EcoStruxure Augmented Operator Advisor (AOA) technology, capable of transferring electrical quantity information from a switchgear to the virtual world and displaying it in the real world with the assistance of an Android phone. The electrical quantity information displayed on the phone is obtained through a PLC that retrieves data from the PM5350 power meter. The result of this research is a prototype that can be used by students to practice monitoring the amount of electricity via a mobile phone in the automation switchgear laboratory. The research findings indicate that when all loads are active, an imbalance of 55.33% occurs. After load balancing adjustments, there is a 39% reduction in the imbalance